Carbon-Encrusted SnS2 Decorated on MXene Nanosheets for Advanced Li-Ion Battery Anodes - Xuezhi Xu; Dong Feng; Liangsa You; Yuhui Xie; Feng Wu; Yuanzhi Zhu; Yi Mei; Delong Xie (Energy Material Advances)
SnS2 stands out as a promising lithium storage anode due to its high specific capacity, low voltage plateau, and cost-effectiveness. However, practical applications are hindered by significant limitations, including low electrical conductivity, volumetric expansion, and sulfur dissolution. In this study, carbon-encrusted SnS2 nanoparticles are anchored onto few-layered MXene via a straightforward ultrasound-assisted ball milling method, yielding SnS2@C/MXene nanocomposites. Kinetic experiments demonstrate that this innovative ball milling approach facilitates the infiltration of SnS2@C into the distorted sites of MXene, effectively curbing interlayer stacking, expediting ion transfer, and bolstering the pseudocapacitance contribution of the anode. Concurrently, the few-layered MXene intertwines with SnS2@C, effectively mitigating the volume fluctuations of the active SnS2@C. As a lithium-ion battery (LiB) anode, SnS2@C/MXene exhibits a specific capacity of 867.1 mAh g−1 after 100 cycles at 0.1 A g−1. Moreover, the SnS2@C/MXene anode demonstrates remarkable reversible specific capacities of 1,162.9, 1,001.0, 838.1, 724.8, 591.5, and 413.9 mAh g−1 under 0.1, 0.2, 0.5, 1, 2, and 5 A g−1, respectively, surpassing those of recently reported SnSx-based LiB anodes. These findings underscore the significant potential of SnS2@C/MXene nanocomposites for high-performance LiBs.